Petrologic subtypes of CM chondrites: Reinvestigation and proposal of subtypes 3.0 to 2.8 - Kimura, Makoto; Imae, Naoya; Komatsu, Mutsumi; Yamaguchi, Akira; Noguchi, Takaaki (2019)
The Tenth Symposium on Polar Science/Poster presentations: [OA] Antarctic meteorites, Wed. 4 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object